(untitled) (REMUNOM, 2025)
The Caracara, Milvago chimachima (Vieillot, 1816), is a bird of prey widely distributed throughout Central and South America, including the entire Brazilian territory. It is a generalist and opportunistic species, with a diverse diet composed of live and dead prey, fruits, seeds, and organic debris. Its prey includes both invertebrates and vertebrates, such as fish, reptiles, birds, and amphibians. During a survey conducted in the Pantanal subregion of Aquidauana, Mato Grosso do Sul, on October 24, 2025, a trophic interaction was observed between an adult female M. chimachima and an adult male Physalaemus biligonigerus. The female landed on a fence carrying the amphibian in her beak and vocalized until a juvenile M. chimachima approached, took the frog from the adult’s beak, and partially ingested it. The observation occurred in a flooded area with lakes undergoing drying, where amphibians were commonly seen vocalizing or moving between water bodies, increasing their vulnerability to predators. During the breeding period, male amphibians accumulate lipids used as energy reserves, making them highly nutritious prey. Thus, the availability and high energetic value of these prey items may enhance the feeding success of birds during the parental care period. This behavior suggests that M. chimachima may synchronize chick-feeding activities with the reproductive season of amphibians, taking advantage of their abundance and nutritional value. This study represents the first documented record of Physalaemus biligonigerus predation by Milvago chimachima, contributing to the understanding of trophic interactions and feeding behavior in this falconid species.